2013
DOI: 10.1590/1414-431x20132932
|View full text |Cite
|
Sign up to set email alerts
|

Relative performance of the two hands in simple and choice reaction time tasks

Abstract: There is evidence that the left hemisphere is more competent for motor control than the right hemisphere. This study investigated whether this hemispheric asymmetry is expressed in the latency/duration of sequential responses performed by the left and/or right hands. Thirty-two right-handed young adults (16 males, 16 females; 18-25 years old) were tested in a simple or choice reaction time task. They responded to a left and/or right visual target by moving their left and/or right middle fingers between two key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…A strong tendency towards a faster response with the right (compared with the left) hand was also found. Previous evidence has shown that simple RTs are not often affected by the hand dominance [89]. This result is also consistent with the hypothesis of left-hemispheric dominance for action selection [90,91].…”
Section: Discussionsupporting
confidence: 90%
“…A strong tendency towards a faster response with the right (compared with the left) hand was also found. Previous evidence has shown that simple RTs are not often affected by the hand dominance [89]. This result is also consistent with the hypothesis of left-hemispheric dominance for action selection [90,91].…”
Section: Discussionsupporting
confidence: 90%
“…First, we found a faster left-hand response in the right-handed participants, whereas a bulk of literature suggests the faster right-hand response (see Ref. 4 for the literature review). Second, motor preparation would affect RT regardless of the stimulus ambiguity.…”
Section: Discussionmentioning
confidence: 69%
“…Thus, subjects demonstrate LH dominance when processing words, whereas face processing induces RH dominance 3 . The motor functions are contralateral, defining better performance of the right hand than the left hand 4 . Finally, the attentional system exhibits hemispheric lateralization.…”
Section: Introductionmentioning
confidence: 99%
“…3A). Additionally, there is a large amount of contradictory evidence that shows that the dominant right hand is superior to the left hand when considering reaction times (Barthelemy & Boulinguez, 2001;Mieschke, Elliott, Helsen, Carson, & Coull, 2001;Nisiyama & Ribeiro-do-Valle, 2014). Another potential explanation for this discrepancy is that use of the left hand to input responses by our right-handed participants may have resulted in a distraction or disruption in sensorimotor integration and left-right discrimination that was specific to images of left hands.…”
Section: Discussionmentioning
confidence: 93%